PENGARUH PROMOSI KESEHATAN KANKER SERVIKS DAN VAKSIN HPV TERHADAP PENGETAHUAN, SIKAP DAN EFIKASI DIRI SISWI DI SMA BAKTI IDHATA JAKARTA SELATAN TAHUN 2022 - Tania Zeta Natasha (2022)
Cervical cancer is a malignancy that grows in cervical cells and considered as one of the highest contributors to mortality from all types of cancer. This cancer could be prevented by avoiding sexual intercourse at an early age and by conducting vaccine against HPV. The purpose of this study was to determine the effect of health promotion on cervical cancer and HPV vaccine on the knowledge, attitudes and self-efficacy of female students at SMA Bakti Idhata. This is a quantitative study with a pre-experimental design as a one group pre-test and post-test design at SMA Bakti Idhata in May 2022. The population in this study were students in grades 10 and 11, and the sample of this study was gathered by using the technique simple random sampling of 70 students. Data analysis used univariate and bivariate analysis with Wilcoxon test at 95% confidence level. The results showed that p-value = 0.000 on the knowledge and attitude, and p-value = 0.001 on the self-efficacy. So, it can be concluded that there is an effect of health promotion on knowledge, attitudes and self-efficacy. It is hoped that with the acquisition of knowledge, attitudes, and self-efficacy, it will be applied by vaccinating anti HPV as a step to prevent cervical cancer as early as possible.